A Benders based rolling horizon algorithm for a dynamic facility location problem. (August 2016) - Marufuzzaman, Mohammad; Gedik, Ridvan; Roni, Mohammad S.
Highlights: We study capacitated dynamic facility location problem (DFLP). We propose a heuristic, a pure and a hybrid Benders algorithm to solve the DFLP. We test our techniques over the extended benchmark instances. Unlike other methods, the hybrid Benders algorithm offers high quality solutions. Abstract: This study presents a well-known capacitated dynamic facility location problem (DFLP) that satisfies the customer demand at a minimum cost by determining the time period for opening, closing, or retaining an existing facility in a given location. To solve this challenging NP -hard problem, this paper develops a unique hybrid solution algorithm that combines a rolling horizon algorithm with an accelerated Benders decomposition algorithm. Extensive computational experiments are performed on benchmark test instances to evaluate the hybrid algorithm's efficiency and robustness in solving the DFLP problem. Computational results indicate that the hybrid Benders based rolling horizon algorithm consistently offers high quality feasible solutions in a much shorter computational time period than the stand-alone rolling horizon and accelerated Benders decomposition algorithms in the experimental range.